ENHANCING ATC HANDOVER-TAKEOVER COMPETENCY: EDUCATIONAL STRATEGIES TO MITIGATE LOSS OF SEPARATION RISKS - Hafidz K. Jati; Surya Tri Saputra; Martha Saulina (SOSIOEDUKASI, 2026)
The handover–takeover (HOTO) process in Air Traffic Control (ATC) operations is a critically important transition point for safety, particularly concerning the risk of loss of separation between aircraft. This study conducts a critical analysis of the principles, rotation patterns, human factors, and technical constraints that influence the effectiveness of information transfer and situational awareness during HOTO. By using a literature-based study method drawing from SKYbrary sources, incident reports, and aviation safety references, this research found that imperfections in the HOTO process, such as inadequate overlap time, incomplete communication, social distractions, and equipment adjustment errors, can increase the probability of traffic conflicts. The findings indicate that HOTO is one of the weak links in the ATC safety system, requiring reinforcement in procedural aspects, supporting technology, rotation design, and safety culture. Mitigation recommendations are aimed at improving procedure standardization, implementing stricter checklists, situational awareness training, and supervisor oversight in complex traffic conditions.